2022
DOI: 10.3389/fmolb.2022.1045548
|View full text |Cite
|
Sign up to set email alerts
|

Regulation mechanism of ferroptosis and its research progress in tumor immunotherapy

Abstract: Ferroptosis is a novel regulatory cell death, which is characterized by iron dependency and mainly caused by accumulation of intracellular lipid peroxides and reactive oxygen species. Ferroptosis plays an important role in the occurrence and development of a variety of malignant tumors, especially in anti-tumor treatment. As an emerging treatment method, the immunotherapy has been widely applied in the clinical practice, and the role of ferroptosis in tumor immunotherapy has been gradually explored. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Ferroptosis differs from other cell death modalities in many ways and the regulatory mechanisms are complex and diverse. Studies have shown that it is mainly related to cellular metabolic regulation, gene regulation, associated autophagy, and other compounds that have both inductive and inhibitory effects on ferroptosis (Xu et al, 2022). Among them, the cellular metabolic regulatory system is mainly involved in three classical mechanisms, namely, imbalance of iron metabolism, dysregulation of the amino acid antioxidant system, and lipid peroxidation pooling (Deng et al, 2023).…”
Section: Overview Of Ferroptosis and Regulatory Mechanismsmentioning
confidence: 99%
“…Ferroptosis differs from other cell death modalities in many ways and the regulatory mechanisms are complex and diverse. Studies have shown that it is mainly related to cellular metabolic regulation, gene regulation, associated autophagy, and other compounds that have both inductive and inhibitory effects on ferroptosis (Xu et al, 2022). Among them, the cellular metabolic regulatory system is mainly involved in three classical mechanisms, namely, imbalance of iron metabolism, dysregulation of the amino acid antioxidant system, and lipid peroxidation pooling (Deng et al, 2023).…”
Section: Overview Of Ferroptosis and Regulatory Mechanismsmentioning
confidence: 99%
“…Ferroptosis is a type of Fe 2+ -dependent cell death that damages polyunsaturated fatty acid-containing phospholipids in cellular membranes mediated by lipid peroxidation (LPO) [ 90 ]. In recent years, increasing numbers of natural and synthetic drugs related to ferroptosis have been identified [ 91 ].…”
Section: The Application Of Metal Ion-based Antitumor Therapeutics An...mentioning
confidence: 99%
“…An innovative ferroptosis mutagen is the natural substance β-elemene, which is effective against human colorectal cancer (CRC) cells with KRAS mutation and inhibits tumor growth by inducing ferroptosis. Combining β-elemene with cetuximab could potentially provide a therapeutic alternative for CRC patients with RAS mutation [ 24 ].
Fig.
…”
Section: Signaling Mechanisms Linked To Cancermentioning
confidence: 99%